Development of a motorized skateboard / Nurzarifah Athirah Zamanhuri - Zamanhuri, Nurzarifah Athirah (2024)
From this project the safety and environmental effect of motorized skateboards were investigated. According to findings, many individuals in the community are concerned about the safety of these skateboards, which may reach high speeds and are sometimes difficult to manage. It is also discovered that motorized skateboards have a detrimental influence on the environment since they run on batteries and energy. To address these issues, a novel motorized skateboard were proposed so that it can be more closely controlled, if not outright outlawed, in order to safeguard the safety of riders and pedestrians while also reducing their environmental effect. Hence, the idea that has been made for doing this project is design and fabrication of motorized skateboard. It was made through a lot of machining process to make it happen. Such as, Welding, drilling and cutting. Besides, the method that use for this project is motorized skateboard with remote control.